A Comparative Analysis of Western and Islamic Developmental Psychology: Analisis Perbandingan Psikologi Perkembangan Barat dan Islam - Eka Chandra Oktaviani; Muhammad Fajar Abdul Aziz (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2024)
Understanding the developmental psychology of individuals is essential for comprehending their growth and behavior throughout life. This study highlights the comparative perspectives of Western and Islamic psychology, both of which aim to understand human behavior but differ in their philosophical, methodological, and spiritual foundations. Western psychology, rooted in ancient Greek thought and later developed through empirical sciences, emphasizes observable behaviors, mental processes, and physiological mechanisms. Key paradigms include psychoanalysis, behaviorism, and humanism, with a focus on rationality and empirical methods. In contrast, Islamic psychology integrates spiritual dimensions, drawing from the Quran and Hadith, and emphasizes the balance of physical, emotional, mental, and spiritual aspects to achieve holistic well-being. Prominent Islamic scholars such as Al-Ghazali and Ibnu Sina contributed significantly to understanding human nature through concepts like nafs (self) and qalb (heart). Methodologically, Western psychology relies on empirical research, experiments, and observable data, while Islamic psychology combines rationality, spiritual practices, and reflection, emphasizing divine guidance as the ultimate source of knowledge. Findings suggest that integrating these approaches can provide a comprehensive framework for addressing psychological challenges, particularly in multicultural societies like Indonesia, where spiritual values are deeply embedded. This synthesis offers valuable insights into promoting mental and spiritual well-being, highlighting the importance of aligning scientific advancements with ethical and spiritual considerations. The study concludes that a collaborative approach between Western and Islamic psychology fosters a deeper understanding of human nature and offers practical solutions for enhancing individual and societal well-being.